Population abundance of recovering humpback whales Megaptera novaeangliae and other baleen whales in Scotia Arc, South Atlantic - Baines, Mick; Kelly, Natalie; Reichelt, Maren; Lacey, Claire; Pinder, Simon; Fielding, Sophie; Murphy, Eugene; Trathan, Phil; Biuw, Martin; Lindstrøm, Ulf; Krafft, Bjørn A.; Jackson, Jennifer A. (Marine Ecology Progress Series, 2021)
Funding: This study forms part of the ecosystems component of the British Antarctic Survey, Polar Science for Planet Earth Programme, funded by the Natural Environment Research Council. This work received funding support from the Foreign, Commonwealth and Development Office, as part of the Overseas Territories Blue Belt Programme, the South Georgia Heritage Trust and from Darwin PLUS award DPLUS057. The data collected from the RV ‘Kronprins Haakon’ work was supported by the Norwegian Ministry of Trade, Industry and Fisheries (NFD, via project number 15208), the Institute of Marine Research (IMR) and the IMR project Krill (project number 14246). The data collected from the FV ‘Cabo de Hornos’ was financed by the Association of Responsible Krill Harvesting Companies (ARK, www.ark-krill.org), Aker Biomarine AS (www.akerbiomarine.com), NFD via project number 15208 and the IMR project Krill. Following the cessation of whaling, South Atlantic populations of humpback Megaptera novaeangliae and some other baleen whale species are recovering, but there has been limited monitoring of their recovery in the Scotia Arc, a former whaling epicentre and a hotspot for Antarctic krill Euphausia superba. To inform the management of krill fisheries, up-to-date assessment of whale biomass and prey consumption is essential. Using a model-based approach, we provide the first estimates of whale abundance and krill consumption for South Georgia and the South Sandwich Islands and total abundance of humpback whales across their southwestern Atlantic feeding grounds, using data collected in 2019. Humpback whale abundance was estimated at 24543 (coefficient of variation, CV = 0.26; 95% CI = 14863-40528), similar to that measured in Brazil on the main wintering ground for this population. The abundance of baleen whales in South Georgia and the South Sandwich Islands, including those not identified to species level, was estimated at 43824 (CV = 0.15, 95% CI = 33509-59077). Based on the proportion of humpback whales identified during the ...